Evolution of space drones for planetary exploration: A review. (February 2018) - Hassanalian, M.; Rice, D.; Abdelkefi, A.
Abstract: In the past decade, there has been a tendency to design and fabricate drones which can perform planetary exploration. Generally, there are various ways to study space objects, such as the application of telescopes and satellites, launching robots and rovers, and sending astronauts to the targeted solar bodies. However, due to the advantages of drones compared to other approaches in planetary exploration, ample research has been carried out by different space agencies in the world, including NASA to apply drones in other solar bodies. In this review paper, several studies which have been performed on space drones for planetary exploration are consolidated and discussed. Design and fabrication challenges of space drones, existing methods for their flight tests, different methods for deployment and planet entry, and various navigation and control approaches are reviewed and discussed elaborately. Limitations of applying space drones, proposed solutions for future space drones, and recommendations are also presented and discussed.